Volume 1: Turbomachinery 1994
DOI: 10.1115/94-gt-126
|View full text |Cite
|
Sign up to set email alerts
|

Rim Sealing of Rotor-Stator Wheelspaces in the Presence of External Flow

Abstract: G axial width of cavity divided byPresented at the International Gas Turbine and Aeroengine Congress and Exposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 13 publications
1
30
1
Order By: Relevance
“…Fig. 12 shows a comparison of results from the simple model with the data given by Chew et al (1994). In this case the pressure asymmetry in the annulus is caused by a row of 18 guide vanes at different axial positions (NGV=1 or 3) upstream of the seal.…”
Section: Stretched Axial Coordinatementioning
confidence: 94%
See 3 more Smart Citations
“…Fig. 12 shows a comparison of results from the simple model with the data given by Chew et al (1994). In this case the pressure asymmetry in the annulus is caused by a row of 18 guide vanes at different axial positions (NGV=1 or 3) upstream of the seal.…”
Section: Stretched Axial Coordinatementioning
confidence: 94%
“…Campbell, unpublished work). However, Chew et al (1994) concluded that this method overpredicted the level of ingestion and attributed this to the neglect of inertial effects associated with the swirl component of velocity. This conclusion drew on experimental data and the results of CFD calculations which showed the influence of the inertial terms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 53 shows a typical aero multistage turbine cavity section. Several experimental studies have been reported that consider both simplified and complex disk cavity configurations (e.g., Chen; 127 Chew et al 128,129 Graber et al, 130 and Johnson et al 131,132 ). Cavity sealing is complex and has a significant effect on component and engine performance and life.…”
mentioning
confidence: 99%